Correlation between endoscopic activity ındices and meteorological parameters in ulcerative colitis - Uslu, Muhammed Fuad; Timurkaan, Esra Suay; Timurkaan, Mustafa; Yilmaz, Mustafa; Dengesik, Emrullah (Bayrakol Medical Publisher, 2025)
Aim: The present study aimed to determine the correlation between the Mayo Endoscopic Score (MES), the validated Ulcerative Colitis Endoscopic Severity Index (UCEIS) and seasonal parameters in ulcerative colitis (UC), the prognosis of which is characterized by attacks. Material And Methods: In the single-center and retrospective study, demographics of the patients who underwent colonoscopy between 2019 and 2023, MES and UCEIS figures, daily and fifteen-day average temperatures (in degrees Celsius), daily average atmospheric pressure (in millibars), daily average humidity (in percentages), and maximum wind speed (in meters per second) were analyzed. Result: The study was conducted with 103 18-92 years old patients whose average age was 48.25 +/- 17.09. 59.2% (n=61) of the participants were male (Female/Male= 42/61) and there was no difference between the participants based on gender (p=0.076). The maximum number of participants (12.9%; n = 13) presented in October, and the minimum presented in July (3.9%; n = 4). It was determined that there was no correlation between MES and UCEIS, and daily and fifteen-day average temperatures, humidity, and pressure. There was no difference between the UCEIS based on the season (p = 0.110); however, there was a significant difference between MES (p = 0.037) in autumn and summer (p = 0.04). Discussion: It was determined that MES differed based on the season, the difference was between autumn and summer. However, UCEIS did not differ based on the season.
Keywords: Ulcerative Colitis; Colonoscopy; Mes; Uceis; Meteorological Parameters